A glucogalactomannan isolated from Agaricus bisporus induces apoptosis in macrophages through the JNK/Bim/caspase 3 pathway. Issue 9 (17th August 2018) - Zhao, Xiaotong; Fang, Leilei; Liu, Danting; Lai, Changjiangsheng; Zhang, Yanqing; Zhou, Aimin; Xie, Junbo
Abstract : Agaricus bisporus is one of the most important edible and medicinal mushrooms in the world. Abstract : Agaricus bisporus is one of the most important edible and medicinal mushrooms in the world. It has been well known that Agaricus bisporus has an immunoregulatory role, but its active ingredients have not been completely identified. In this study, a glucogalactomannan named TJ3 was isolated and purified from Agaricus bisporus . TJ3 (827 kDa) is composed of mannose, galactose, glucose and xylose in the ratio 28.26 : 27.82 : 20.88 : 9.87 mainly joined by β-linkages. Functional analysis of TJ3 revealed that it effectively induced apoptosis in RAW 264.7 cells, a mouse macrophage cell line. Cell apoptosis was determined by an Annexin V/PI staining assay. After treatment with TJ3 (2 μg mL −1 ) for 16 h, apoptosis was observed in 34% of the Raw cells (9% in the non-treated control cells). TJ3 treatment remarkably increased the production of cleaved caspase-3, PARP and Bim, and decreased the level of Bcl-2 although no obvious change in the level of Bax was observed. Interestingly, further elucidation of the molecular mechanism underlying the role of TJ3 in the induction of apoptosis showed that TJ3 activated the JNK signaling pathway through TLR4 and subsequently promoted the expression of Bim and activation of caspase-3. Our results demonstrate that TJ3 may be a novel active component in Agaricus bisporus responsible for its immunoregulatory role by the induction of macrophage apoptosis.